INTERVENSI GURU TERHADAP EKSPRESI TUTUR SISWA TUNARUNGU - Suko Winarsih (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2014)
This study aims to describe teacher interventions in deaf students’ oral expressions,comprising those in speech acts, speech functions, and speech strategies. It employed thequalitative descriptive approach. The data comprised descriptive and reflective data. Theywere analyzed by means of pragmatics theory, especially clinical pragmatics. The findingsare as follows. First, interventions in speech acts include illocutionary acts, conversationcapabilities, understanding, and narration. Second, interventions in speech functionsinclude directive and facilitative interventions. Third, interventions in speech strategiesinclude context manipulation and pre-symbolic and minimum symbolic interventions.